2016
DOI: 10.1016/j.ijid.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus lugdunensis, a serious pathogen in periprosthetic joint infections: comparison to Staphylococcus aureus and Staphylococcus epidermidis

Abstract: S. lugdunensis is an emerging pathogen with a pathogenicity quite similar to that of S. aureus. This coagulase-negative Staphylococcus must be identified precisely in PJI, in order to select the appropriate surgical treatment and antibiotics .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…Although retrospective data have to be carefully interpreted, they intrigue clinicians, because the results reported in the literature suggest that the mortality rate of S. aureus endocarditis is approximately 20%, whereas the global mortality rate of CoNS endocarditis is approximately 12% (18,19). The occurrence of bone and joint infections appeared recently in retrospective studies describing prosthetic joint infections, particularly knee joint infections (20). Argemi et al 3and Douiri et al (21) showed in two recently published studies that 40% of all clinical samples that tested positive for S. lugdunensis were obtained from patients with proven infections, particularly bone and joint infections.…”
Section: S Lugdunensis Virulence: Growing Evidences From Clinical Stmentioning
confidence: 99%
“…Although retrospective data have to be carefully interpreted, they intrigue clinicians, because the results reported in the literature suggest that the mortality rate of S. aureus endocarditis is approximately 20%, whereas the global mortality rate of CoNS endocarditis is approximately 12% (18,19). The occurrence of bone and joint infections appeared recently in retrospective studies describing prosthetic joint infections, particularly knee joint infections (20). Argemi et al 3and Douiri et al (21) showed in two recently published studies that 40% of all clinical samples that tested positive for S. lugdunensis were obtained from patients with proven infections, particularly bone and joint infections.…”
Section: S Lugdunensis Virulence: Growing Evidences From Clinical Stmentioning
confidence: 99%
“…Among the S lugdunensis PJI episodes (summarized in Table 1), we could identify the site of infection in 84, among which 58 (69%), 24 (28.6%), and 2 (2.4%) episodes were in knees, hips, and other sites, respectively. This observation was previously made by the authors of the largest 2 series of S lugdunensis PJI [2], [29]. Presentation of PJI due to S lugdunensis can vary widely between acute symptoms such as fever and local site inflammation to unexplained dull aching pain at the site of surgery.…”
Section: Discussionmentioning
confidence: 62%
“…Presentation of PJI due to S lugdunensis can vary widely between acute symptoms such as fever and local site inflammation to unexplained dull aching pain at the site of surgery. Delay between time of surgery and presentation can be as short as 3 weeks [29] or as long as 10 years [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations